2013
DOI: 10.1038/cgt.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Improved cytotoxic T-lymphocyte immune responses to a tumor antigen by vaccines co-expressing the SLAM-associated adaptor EAT-2

Abstract: The signaling lymphocytic activation molecule-associated adaptor Ewing's sarcoma's-activated transcript 2 (EAT-2) is primarily expressed in dendritic cells, macrophages and natural killer cells. Including EAT-2 in a vaccination regimen enhanced innate and adaptive immune responses toward pathogen-derived antigens, even in the face of pre-existing vaccine immunity. Herein, we investigate whether co-vaccinations with two recombinant Ad5 (rAd5) vectors, one expressing the carcinoembryonic antigen (CEA) and one ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Several of the identified genes had demonstrated functional relationships to cytotoxic responses, including the inhibitory killer cell immunoglobulinlike receptor KIR2DL1, the NK cell activating receptor CLEC2D [54], and the NK-cell signaling adaptor EAT-2 [55], and many more were protein-protein interaction network neighbors of genes that comprise "Cytotoxicity", "T cells", and "Lymphoid lineage" transcriptional modules. Consistent with the identified association between EAT-2 expression and CD8+ T-cell responses, it was recently reported that adenoviral expression of EAT-2 as part of a vaccine strategy enhanced vaccine-induced T-cell responses [56,57]. Furthermore, integration of these genes with published innate and immunogenicity data for the yellow fever vaccine [18] revealed that two of them (CRIP3 and NPB) exhibited expression responses that were consistently associated with impaired CD8+ T-cell immunogenicity.…”
Section: Case Study 2: Longitudinal Integration Of Innate and Adaptivmentioning
confidence: 67%
See 1 more Smart Citation
“…Several of the identified genes had demonstrated functional relationships to cytotoxic responses, including the inhibitory killer cell immunoglobulinlike receptor KIR2DL1, the NK cell activating receptor CLEC2D [54], and the NK-cell signaling adaptor EAT-2 [55], and many more were protein-protein interaction network neighbors of genes that comprise "Cytotoxicity", "T cells", and "Lymphoid lineage" transcriptional modules. Consistent with the identified association between EAT-2 expression and CD8+ T-cell responses, it was recently reported that adenoviral expression of EAT-2 as part of a vaccine strategy enhanced vaccine-induced T-cell responses [56,57]. Furthermore, integration of these genes with published innate and immunogenicity data for the yellow fever vaccine [18] revealed that two of them (CRIP3 and NPB) exhibited expression responses that were consistently associated with impaired CD8+ T-cell immunogenicity.…”
Section: Case Study 2: Longitudinal Integration Of Innate and Adaptivmentioning
confidence: 67%
“…It is also possible to directly include host modulatory components within the vaccines themselves in order to effectively reprogram the host. As mentioned above, expressing an NK-cell signaling adaptor [56,57] as part of an adenoviral vaccine strategy enhanced vaccineinduced CD8+ T-cell responses. Collectively, these studies suggest that it will be possible to employ systems vaccinology to identify critical nodes in the host response, and then construct improved vaccines that specifically activate or suppress those nodes.…”
Section: Perturbations: Closing the Loopmentioning
confidence: 95%
“…We and others have verified that rAd5-CEA vaccination of murine and human subjects induces significant CEA-specific CMI [7, 8, 27]. To examine if the addition of rAd5-rEA to a TAA-expressing vaccine would further promote anti-TAA CMI responses, we treated mice with rAd5-CEA and an equivalent dose of either rAd5-rEA or a GFP-expressing control adenovirus vector (rAd5-GFP).…”
Section: Resultsmentioning
confidence: 99%
“…ELISpot mouse IFNγ and IL-2 kits (eBioscience, San Diego, CA), as previously described [27]. In brief, splenocytes (5 × 10 6 cells/well) from individual mice were incubated on capture antibody pre-treated plates with individual CEA peptides or a CEA peptide pool (0.4 μg/well).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation